KOSAKATA BAHASA GAUL SISWA SEKOLAH DASAR KELAS TINGGI - Arfi Yana; Nurlela .; Gustianingsih . (Universitas Negeri Medan, 2018)
Abstract : The Slang Vocabulary of High Grade Elementry School students. The aimed to describe the slang vocabulary of high grade elementryschool students. Source of data was the text from students essay. The data was analyzed by word class theory and sosiolinguistic questionnaire. The result showed that the word class of slang vocabulary involve: verbs (36,7%), adjectives (11,7%), nouns (6,7%), pronouns (6,7%), numeralia (3,3%), adverbs (8,3%), interogativa (1,7%), demonstrativa (3,3%), conjuction (3,3%), fatis category (16,7%), and interjection (1,7%).Acquistion factors of the slang students were parent (4,5%), sister/brother (15,8%), playmates (16,5%), schoolmates (20,3%), television (26,3%), and facebook (16,5).Keywords : Word Class, Slang, SosiolinguisticAbstrak : Kosakata Bahasa Gaul Siswa Sekolah Dasar Kelas Tinggi. Tujuan penelitian adalah mendeskripsikan kosakata bahasa gaul siswa kelas tinggi. Sumber data penelitian ini berupa data teks melalui karangan siswa. Data dianalisis menggunakan teori kelas kata dan kuesioner sosiolinguistik. Hasil penelitian menunjukkan bahwa kelas kata bahasa gaul siswa SD kelas tinggi meliputi: verba (36,7%), adjektiva (11,7%), nomina (6,7%), pronomina (6,7%), numeralia (3,3%), adverbia (8,3%), interogativa (1,7%), demonstrativa (3,3%), konjungsi (3,3%), kategori fatis (16,7%), dan interjeksi (1,7%). Faktor pemerolehan bahasa gaulsiswa yaituorang tua (4,5%), kakak/abang (15,8%), teman sepermainan (16,5%), teman sekolah (20,3%), televisi (26,3%), dan facebook (16,5).Kata kunci: Kelas Kata, Bahasa Gaul, Sosiolinguistik